Students’ Perceptions About The Importance of Group Study in The Tertiary Educational Institutions of Bangladesh - Rahman, Md. Anisur; Humaidi, M. Nurul (Jurnal al-Thullab, 2023)
This study is grounded in the need to shift from teacher-centered to student-centered learning approaches in tertiary education, particularly in Bangladesh, where collaborative learning remains underutilized. The research aims to examine students’ perceptions of the importance of group study in supporting their academic development. A mixed-method design was employed, involving 80 first-year honors students from an Islamic college affiliated with Bangladesh National University. Data were collected through questionnaires, interviews, observations, and focus group discussions to ensure comprehensive and reliable findings. The results reveal that most students perceive group study positively, as it enhances their understanding, engagement, communication skills, and overall academic performance. However, several challenges were identified, including unequal participation and limited organizational skills among some group members. These findings suggest that structured and well-managed group study can significantly improve student-centered learning practices. The study contributes to the development of collaborative learning strategies in higher education and highlights the importance of institutional support, effective facilitation, and student readiness in optimizing the benefits of group study for academic success.